Cell culture techniques in gastrointestinal research: Methods, possibilities and challenges - Gaur Preksha (Wolters Kluwer Medknow Publications, 2021)
Cell culture is one of the most valuable tools which is being applied in both fundamental and applied gastrointestinal research. The cells are isolated from their natural location (in vivo) and further propagated in vitro or artificial environment and studied. Over the years, several methods have been devised to isolate animal cells derived from the gut and culture them in vitro to study the functions and biology in the context of complex gastrointestinal diseases. This mini-review briefly describes the types and methods of cell culture covering the simplest monoculture models to more recent 3D organoid models, highlighting its importance in personalized precession medicine and other aspects of translational research. It also throws light upon the major challenges and outlines the future directions for using cell culture as a model system.